On The Special Administrative Disputes in Indonesia: Legal Certainty or Legal Uncertainty - Ariyanto, Bambang; Sukardi, Sukardi; Ristiawati, Rosa (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The evolution of State Administrative Court Procedure Law is highly dynamic, in accordance with the implementation of multiple laws and regulations that govern the State Administrative Court. In the past, the procedural law of the TUN Court consistently made reference to Law no. 5 of 1986 in connection with Law no. 9 of 2004 and Law no. 51 of 2009. However, the procedural law of the State Administrative Court has undergone further development. Furthermore, there are already other sector-specific rules that have been established to particularly govern the resolution of some administrative court issues. Examinations that are not categorized as Ordinary Events, Quick Events, or Short Events are generally referred to as Special administrative court Disputes. The question at hand is whether the presence of this unique administrative court  disagreement ensures legal assurance under the procedural law at the administrative Court, encompassing the mechanism for resolving such disputes. The study methodology employed is normative juridical, utilizing both a legislative approach and a conceptual approach. The Special TUN dispute category encompasses requests for abuse of authority tests, positive fake requests, public information disputes, land acquisition disputes for development in the public interest, and general electoral process issues. Among the various disputes in the Special State Administrative Court, the issue of the Positive Fictitious Petition lacks legal certainty. This is because the procedural law is governed by a Presidential Regulation that is not consistent with the 1945 Constitution of the Republic of Indonesia, which stipulates that judicial power must be regulated by legislation.